THE IMPACT OF PARENTING PRACTICES ON COPING SKILLS AND RESILIENCE: A STUDY OF DEPRESSION AMONG YOUNG ADULTS - Kala, Deepiksha; Maheshwari, Kiran (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Parenting practices play a major role in shaping the psychological well-being of young adults. As we know that emerging adulthood is marked by so many challenges, including identity exploration, academic and career demands, and shifting social roles, which may increase vulnerability to depression. With an emphasis on depression among young adults in India, this study examines how parenting styles affect coping mechanisms and resilience. Theories of coping, resilience, and depression’s cognitive frameworks will all help in our comprehension of how these factors affect young adults. In order to reduce symptoms of depression, the study examines how positive parenting techniques like engagement, warmth, and autonomy can help children become more resilient and develop adaptive coping mechanisms. Findings from different sources indicated that positive parenting practices significantly predict resilience and coping, which in turn buffer against depression. The implications highlight that parent’s guidance and support is important to enhance psychological and social well-being in young adults. It is also important for parents to identify early signs and symptoms of depression in children.